Insights Into Episodic Exhumation of the Western Tibetan Plateau Since the Late Cretaceous From Low‐Temperature Thermochronology. Issue 12 (29th November 2022) - Xu, S. Y.; Dai, J. G.; Li, H. A.; Liu, B. R.; Han, X.; Wang, C. S.
Abstract: The western Tibetan Plateau (TP) is characterized by low relief with high elevation separated by deep river valleys. When and how this characteristic topography developed remains ambiguous. Here, we present apatite (U‐Th)/He and fission‐track ages from three groups of samples with different geomorphic and geological settings. Thermal histories and exhumation rates were extracted from the thermochronological data. An early stage of exhumation (ca. 0.1 km/Ma) during 70–40 Ma was recorded by all samples, followed by slow exhumation (0.03–0.06 km/Ma) since the Eocene for the sample farthest away from faults and incised valley. The second stage of faster exhumation (ca. 0.13–0.15 km/Ma) during 30–23 Ma was revealed by samples from the hanging wall of thrust faults, whereas the third stage of exhumation during 15–12 Ma (ca. 0.1 km/Ma) was identified from samples in the Dingzi Zangbo valley. Combined with the regional geological setting, we propose that (a) the Late Cretaceous‐Early Eocene exhumation in the western TP was related to regional thrust‐induced crustal thickening and led to the formation of the proto‐TP; (b) the proto‐TP was modified by local structures and river incision. The Oligocene exhumation might be caused by local thrust activity, whereas the Miocene exhumation might be related to the transition from internal to external drainage. The continuous activity of the Karakoram fault resulted in another reorganization of drainage which led to the slow exhumation since 9 Ma. Our results highlight that tectonic and drainage network reorganization play an important role in shaping the geomorphology of the western TP. Plain Language Summary: The formation of high‐elevation and low‐relief landscapes with deep river valleys in the western TP remains ambiguous. We present new apatite (U‐Th)/He and fission‐track thermochronological data and thermal modeling. Our results revealed three stages of rapid exhumation and one regional slow exhumation since the Eocene, which can provide robust constraints on the geological and geomorphic evolution of the western TP. The high‐elevation and low‐relief landscapes of the western TP were established since the Eocene, which was further modified by local thrust activity during 30–23 Ma and river incision during Miocene (ca. 19–17, ca.15–12, ca. 11–9 Ma). The tectonic activity and drainage reorganization control the geomorphic evolution of the western TP. Key Points: After Late Cretaceous‐Early Cenozoic rapid exhumation, most of the western Tibetan Plateau (TP) became a part of a proto‐TP since the Eocene Thrust fault activity during the Oligocene triggered exhumation and increased the local relief The transition from internal to external drainage during early Miocene increased valley incision and produced the local relief